Modulation of Adaptive Cognitive Control by Prefrontal High-Definition Transcranial Direct Current Stimulation in Older Adults. (2nd May 2019) - Gbadeyan, Oyetunde; Steinhauser, Marco; Hunold, Alexander; Martin, Andrew K; Haueisen, Jens; Meinzer, Marcus
Abstract: Objective: Adaptive cognitive control frequently declines in advanced age. Because high-definition transcranial direct current stimulation (HD-tDCS) of the right dorsolateral prefrontal cortex (DLPFC) improved cognitive control in young adults, we investigated if this montage can also improve cognitive control in older individuals. Method: In a double-blind, sham HD-tDCS controlled, cross-over design, 36 older participants received right DLPFC HD-tDCS during a visual flanker task. Conflict adaptation (CA) effects on response time (RT) and error rates (ER) assessed adaptive cognitive control. Biophysical modeling assessed the magnitude and distribution of induced current in older adults. Results: Active HD-tDCS enhanced CA in older adults. However, this positive behavioral effect was limited to CA in ER. Similar to results obtained in healthy young adults, current modeling analysis demonstrated focal current delivery to the DLPFC with sufficient magnitude of the induced current to modulate neural function in older adults. Discussion: This study confirms the effectiveness of HD-tDCS to modulate adaptive cognitive control in advanced age.